2021
DOI: 10.2196/18590
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Use Digital Health Tools in Patient Care Among Health Care Professionals and Students at a University Hospital in Saudi Arabia: Quantitative Cross-sectional Survey

Abstract: Background The adoption rate of digital health in the health care sector is low in many countries. A facilitating factor for successful implementation and adoption of digital health is acceptance by current and future health care professionals. Objective This study was conducted to identify factors associated with willingness to use digital health tools in patient care among health care professionals and students. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 40 publications
7
45
0
Order By: Relevance
“…For the growing utility and complexity of telemedicine, medical education curricula that integrate telemedicine training concepts early during medical training may help to increase trainees' familiarity with telemedicine systems in the future. This result was consistent with study conducted in USA [ 5 ], Ethiopia [ 25 ], Saudi Arabia [ 26 ] and China [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…For the growing utility and complexity of telemedicine, medical education curricula that integrate telemedicine training concepts early during medical training may help to increase trainees' familiarity with telemedicine systems in the future. This result was consistent with study conducted in USA [ 5 ], Ethiopia [ 25 ], Saudi Arabia [ 26 ] and China [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, 31% (21/68) of interns agreed or strongly agreed that digital health requires more mental effort, and 46% (31/68) believed that telehealth could increase their workload. The findings related to the complexity of telehealth use in this study are consistent with the findings reported in previous studies [ 21 , 30 ]. A study conducted in Saudi Arabia by Thapa et al [ 30 ] reported that students perceived that the use of eHealth would increase work-related stress and could delay responses to patients’ needs.…”
Section: Discussionsupporting
confidence: 93%
“…The findings related to the complexity of telehealth use in this study are consistent with the findings reported in previous studies [ 21 , 30 ]. A study conducted in Saudi Arabia by Thapa et al [ 30 ] reported that students perceived that the use of eHealth would increase work-related stress and could delay responses to patients’ needs. In addition, this study found that more than half of the interns 54% (37/68) believed that telehealth might threaten the information privacy of patients, compared with 66% reported by Birukand Abetu [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have for example found that attitude toward ICT and contextual factors are important and could provide further insights when integrating ICT in clinical work. 40–42 …”
Section: Discussionmentioning
confidence: 99%